Gln-362 of Angiopoietin-2 Mediates Migration of Tumor and Endothelial Cells through Association with α5β1 Integrin - Lee, Hyo Seon (J Biol Chem, 2014)
Angiopoietin-2 (Ang-2) not only regulates angiogenesis by binding to its well known receptor Tie2 on endothelial cells but also controls sprouting of Tie2-negative angiogenic endothelial cells and invasion of Tie2-negative non-endothelial cells by binding to integrins. However, the molecular mechanism of the Ang-2/integrin association has been unclear. In this study, we found that the Gln-362 residue of Ang-2 was essential for binding to α5β1 integrin. A Q362E Ang-2 mutant, which still bound to Tie2, failed to associate with α5β1 integrin and was unable to activate the integrin downstream signaling of focal adhesion kinase. In addition, unlike wild-type Ang-2, the Q362E Ang-2 mutant was defective in mediating invasion of Tie2-negative glioma or Tie2-positive endothelial cells. Furthermore, the tailpiece domain of the α5 subunit in α5β1 integrin was critical for binding to Ang-2. Taken together, these results provide a novel insight into the mechanism of integrin regulation by Ang-2, which contributes to tumor invasion and endothelial cell migration in a Tie2-independent manner.